Research Progress on the Role of Microglia Membrane Proteins or Receptors in Neuroinflammation and Degeneration - Zhao, Jun-Feng; Ren, Tong; Li, Xiang-Yu; Guo, Tian-Lin; Liu, Chun-Hui; Wang, Xun (Frontiers in Cellular Neuroscience, 2022)
Microglia are intrinsic immune cells of the central nervous system and play dual roles (pro-inflammatory and anti-inflammatory) in the homeostasis of the nervous system. Neuroinflammation mediated by microglia is an important stage of ischemic hypoxic brain injury, cerebral hemorrhage disease, neurodegeneration and neurotumor of the nervous system and runs through the whole course of the disease.Microglial cell membrane protein or receptors are mediated microglia inflammation, the basis of them by identifying the ligands or feel nervous system environment change and increase expression, allosteric activation of downstream signal transduction and produce a series of complex cascade and activated microglia, microglia chemotactic migration and release of proinflammatory factor such as  TNF-α , IL-β, damage to the nervous system and apoptosis of neurons.In this paper, several representative membrane proteins or receptors on the surface of microglia cells are selected to make a review of their structure, function and specific role in one or more neurological diseases, and on this basis, some prospects for novel Coronavirus.